2010
DOI: 10.1111/j.1751-3928.2010.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Mineralization Age of the Fukusen No. 1 Vein, Hishikari Epithermal Gold Deposits, Southern Kyushu, Japan

Abstract: The Fukusen No. 1 vein is located in the southeastern part of the Yamada deposit, Hishikari epithermal gold deposits, southern Kyushu, Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Most LS ores formed in settings where earlier subduction enriched the lithospheric mantle above the subducted plate with volatiles and metals. The LS ores are generally similar in age to the nearby or host volcanic rocks (Hames et al, 2009;Izawa et al, 1990;Leavitt et al, 2004;Tohma et al, 2010). The LS ores are typically hosted by basalt-rhyolite calc-alkaline volcanic rocks in predominantly extensional environments in intra-arc, near-arc, and back-arc postcollisional rifts (Sillitoe and Hedenquist, 2003).…”
Section: Low-sulfidation Epithermal Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most LS ores formed in settings where earlier subduction enriched the lithospheric mantle above the subducted plate with volatiles and metals. The LS ores are generally similar in age to the nearby or host volcanic rocks (Hames et al, 2009;Izawa et al, 1990;Leavitt et al, 2004;Tohma et al, 2010). The LS ores are typically hosted by basalt-rhyolite calc-alkaline volcanic rocks in predominantly extensional environments in intra-arc, near-arc, and back-arc postcollisional rifts (Sillitoe and Hedenquist, 2003).…”
Section: Low-sulfidation Epithermal Depositsmentioning
confidence: 99%
“…Partial melting of this subduction-enriched mantle wedge produced magmas that yielded porphyry and epithermal mineralization (e.g., Richards, 2009;Saunders and Brueseke, 2012). New high-precision geochronology suggests that ore formation was of relatively short duration, perhaps as brief as a few thousand to a few tens of thousands of years (Heinrich, 2006;Saunders, 2010;Simmons and Brown, 2006;Tohma et al, 2010). The LS ores are generally similar in age to the nearby or host volcanic rocks (Hames et al, 2009;Izawa et al, 1990;Leavitt et al, 2004;Tohma et al, 2010).…”
Section: Low-sulfidation Epithermal Depositsmentioning
confidence: 99%
“…ties responsible for major mineralizations at the Koryu deposit ceased by 0.85 Ma. The similar durations of mineralization from two other epithermal Au-Ag deposits were reported: 0.64 million years at the Hishikari deposit (Sekine et al, 2002;Sanematsu et al, 2005;Sanematsu et al, 2006;Tohma et al, 2010) and 0.53 million years at the Cibaliung deposit, Indonesia (Harijoko et al, 2004).…”
Section: Discussionmentioning
confidence: 50%
“…A number of microthermometric studies on quartz and adularia were conducted, largely on samples from the Honko ore zone (e.g., Izawa et al, ; Nagayama, ; Hayashi et al, ), and a few studies each on samples from the Sanjin ore zone (Sanematsu et al, ; Takahashi et al, ) and the Yamada zone (Ueno et al, ; Tohma et al, ). These studies showed that: (i) the homogenization temperatures generally ranged between 150 and 250°C; (ii) the average values (and/or mode values) of homogenization temperatures were within the range 190–215°C, with some exceptions, suggesting that the formation temperature of the veins was generally around 200°C; and (iii) the formation temperatures between the columnar adularia (earliest stage) and the comb quartz (late stage) were similar.…”
Section: Discussionmentioning
confidence: 99%
“…a). The deposit formed during the Pleistocene (0.61–1.25 Ma) (Izawa et al, ; Sanematsu et al, ; Tohma et al, ) within basement sedimentary rocks of the Cretaceous Shimanto Supergroup and the overlying Quaternary volcanic rocks (Fig. b).…”
Section: Geological Setting Of the Metallic Mineralizationmentioning
confidence: 99%